Evaluation of Dental Students' Awareness of Endodontic Procedural Accidents in Babol University of Medical Sciences in 2013-2014 - Mohammad Kashefi Nejad; Maryam Ehsani; Soraya khafri; Habib Abdollahi Kalorazi (Mashhad University of Medical Sciences, 2016)
Background: During root canal treatment procedures, unexpected accidents may be confronted affecting long-term prognosis just as in any other dental treatment. The purpose of this study was to evaluate the knowledge of dental students of accidents and errors during endodontic treatment in Medical University of Babol. Materials and Methods: In this cross-sectional study, 52 senior dental students were examined. Required information was collected with a questionnaire with 20 questions relating causes, prevention, treatment and prognosis of accidents during endodontic treatment. Data was analyzed using descriptive parameters, chi-square test and T-test by the statistical software SPSS Ver.21. Results: The students' knowledge was moderate in all of the fields studied including causes, prevention, treatment and prognosis of accident during endodontic treatment. Their knowledge of the causes of accidents during endodontic treatment was the lowest level and their awareness of the required endodontic treatment was the highest. There were no significant differences (P>0.05) in the average knowledge of students in the four areas of causes, prognosis, prevention and treatment of accidents of endodontic treatment. There was a significant difference in the average knowledge of the causes between male and female dental students (P